REKONSTRUKSI ANDRAGOGI PENDIDIKAN ISLAM MELALUI PEMBELAJARAN TRANSFORMATIF MEZIROW - Ahmad Nawawi, Ahmad Nawawi; Farhad Muhammad, Farhad Muhammad; Kusaeri, Kusaeri (IAIN Ponorogo, 2024)
AbstractIslamic andragogy in Indonesia is experiencing boredom with its pragmatic religious pattern, wanting a renewal in interpreting religious values with a different approach, especially in the field of education which determines the direction of the future, Mezirow’s transformative learning theory makes a breakthrough by reconstructing the values that exist in a person through real experiences that passed it. This research aims to reconstruct Islamic education for adults using Mezirow’s transformative learning theory. This research uses a systematic literature review method by collecting journal articles that match the theme raised and filtering them until they become the main material for reviewing this paper. The research results show that Mezirow’s transformative learning theory can be used to reconstruct Islamic education for adults by applying ten phases/steps in it which have a significant influence on students’ cognitive, emotional and social abilities which is in accordance with Islamic culture. So the use of this theory in learning at various levels of education needs to be considered.AbstrakAndragogi Islam di Indonesia mengalami kejenuhan dengan pola religius pragmatisnya, mengingkan sebuah pembaruan dalam meingterpretasikan nilai agama dengan pendekatan yang berbeda khusunya di bidang pendidikan yang menentukan arah masa depan, teori pembelajran transformatif Mezirow melakukan terobosan dengan merekonstruk nilai yang ada pada diri seseorang melalui pengalaman nyata yang dilaluinya. Penelitian ini bertujuan untuk merekontruksi pendidikan Islam bagi orang dewasa menggunakan teori pembelajaran transformatif Mezirow. Penelitian ini menggunakan metode systematic literature review dengan mengumpulkan jurnal artikel yang sesuai dengan tema yang diangkat dan dilakukan penyaringan hingga menjadi bahan utama dalam mengkaji tulisan ini. Hasil penelitian menunjukkan bahwa teori pembelajaran transformatif Mezirow dapat digunakan untuk merekonstruksi Pendidikan Islam bagi orang dewasa dengan menerapkan sepuluh fase/langkah di dalamnya yang memiki pengaruh signifikan terhadap kemampuan kognitif, emosi, dan sosial siswa yang sesuai dengan kultur islam. Sehingga pengunaan teori ini dalam pembelajaran di berbagai jenjang pendidikan perlu dipertimbangkan